Endothelial-mesenchymal crosstalk drives osteogenic differentiation of human osteoblasts through Notch signaling - Daria Perepletchikova; Polina Kuchur; Liubov Basovich; Irina Khvorova; Arseniy Lobov; Kseniia Azarkina; Nikolay Aksenov; Svetlana Bozhkova; Vitaliy Karelkin; Anna Malashicheva (Cell Communication and Signaling)
Abstract Background Angiogenesis and osteogenesis are closely interrelated. The interaction between endothelial and bone-forming cells, such as osteoblasts, is crucial for normal bone development and repair. Juxtacrine and paracrine mechanisms play key roles in cell differentiation towards the osteogenic direction, assuming the direct effect of endothelium on osteogenic differentiation. However, the mechanisms of this interplay have yet to be thoroughly studied. Methods Isolated endothelial cells (EC) from human umbilical vein and human osteoblasts (OB) from the epiphysis of the femur or tibia were cultured in direct and indirect (separated by membrane) contact in vitro under the osteogenic differentiation conditions. Osteogenic differentiation was verified by RT-PCR, and alizarin red staining. Shotgun proteomics and RNA-sequencing were used to compare both EC and OB under different co-culture conditions to assess the mechanisms of EC-OB interplay. To verify the role of Notch signaling, experiments with Notch modulation in EC were performed by EC lentiviral transduction with further co-cultivation with OB. Additionally, the effect of Notch modulation in EC was assessed by RNA-sequencing. Results EC have opposite effects on osteogenic differentiation depending on the co-culture conditions with OB. In direct contact, EC enhance osteogenic differentiation, but in indirect cultures, EC suppress it. Our proteotranscriptomic analysis revealed that the osteosuppressive effect is related to the action of paracrine factors secreted by EC, while the osteoinductive properties of EC are mediated by the Notch signaling pathway, which can be activated only upon a physical contact of EC with OB. Indeed, in the direct co-culture, the knockdown of Notch1 and Notch3 receptors in EC has an inhibitory effect on the OB osteogenic differentiation, whereas activation of Notch by intracellular domain of either Notch1 or Notch3 in EC has an inductive effect on the OB osteogenic differentiation. Conclusion The data indicate the dual role of the endothelium in regulating osteogenic differentiation and highlight the unique role of the Notch signaling pathway in inducing osteogenic differentiation during cell-to-cell interactions. The findings of the study emphasize the importance of intercellular communication in the regulation of osteoblast differentiation during bone development and maintenance. Graphical Abstract